Inclusive Infrastructure: Assessing the Synergy Between Universal Design Facilities and Neurodiversity-Friendly Human Resource Management - T.D Madingin Situmorang; Mohammad Ali Nugroho Ali Nugroho; Rina Marlina; Ahmad Faisol; Faisal Razak (Pengabdian: Jurnal Abdimas, 2026)
Background. Neurodiversity support requires inclusive workplaces combining physical Universal Design (UD) (e.g., sensory spaces) and neurodiversity-friendly HR practices (e.g., flexible schedules). However, the synergy between these infrastructure and procedural elements is largely underexplored. Purpose. This research assesses the combined impact of UD features and neurodiversity-sensitive HR practices on neurodiverse employees, workplace inclusivity, and related outcomes. Method. A mixed-methods approach using quantitative surveys and qualitative interviews was conducted across 25 organizations, involving both employees and HR managers. Results. Integrating both UD facilities and neurodiversity-friendly HR practices significantly boosted employee satisfaction, engagement, and performance. This combination proved more effective than either factor alone, demonstrating a clear synergistic effect. Conclusion. A holistic approach merging UD infrastructure and HR strategies is crucial for neurodiversity inclusion, enhancing employee well-being and productivity. These findings provide a framework for future research on workplace diversity